SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN TERBAIK MENGGUNAKAN METODE VISE KRITERIJUMSKA OPTIMIZAJICA I KOMPROMISNO RESENJE (VIKOR) BERBASIS WEB (STUDI KASUS : PT. GAYUH MEDIA INFORMATIKA) - Riyan Nopriyana; Joko Riyanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The quality of human resources is one of the supporting factors to increase the performance productivity of a corporate agency. Highly competent human resources can support the level of performance, with performance appraisal, the achievements of each employee will be obtained. To obtain fast and accurate information on employee performance that meets the expected criteria. To solve this problem, a multi-criteria decision-making method was chosen by solving complex and unstructured situations into parts and compiling them using the Vlse Kriterijumska Optimizajica I Kompromisno Resenje (VIKOR) method. ) in the Decision Support System (SPK), the determination of the best employee can be calculated based on the calculation of the weight of each criterion, so that the best employee in the company can be selected quickly.